Understanding and measuring the work‐related quality of life among those working in adult social care: A scoping review. (23rd January 2022) - Silarova, Barbora; Brookes, Nadia; Palmer, Sinead; Towers, Ann‐Marie; Hussein, Shereen
Abstract: The main aim of this scoping review was to understand how work‐related quality of life (WRQoL) in adult social care has been defined and measured in the literature and to map key components of WRQoL among those working in adult social care and similar contexts. The scoping review included studies that: 1‐ focused on WRQoL/work‐related wellbeing (and their synonyms); and 2‐ included adult social care or community health care. We searched existing evidence from November 2019 until July 2020 through an electronic literature search of eight major databases complemented by the grey literature, searching the reference lists and by contacting our existing network of experts in the field. In addition, we repeated the searches to identify any relevant literature published in 2021. Reporting followed the PRISMA Extension for Scoping Reviews (PRISMA‐ScR) checklist. In total, we included 68 publications. These publications indicate that there is an absence of agreement on a definition and measurement of WRQoL in adult social care. Based on a thematic analysis we identified six key components of WRQoL: organisational characteristics; job characteristics; mental wellbeing and health; physical wellbeing and health; spill‐over from work to home; and professional identity. In summary, at the moment, there is no agreement on what WRQoL is and how to measure it in adult social care. As a result, there is very limited evidence on how to improve WRQoL among people working in adult social care. However, this scoping review suggests that there are six key components of WRQoL that researchers may consider to include in their future studies.